The value of the product expression (-2x-9y²)(-4x-3) is 8x² + 6x + 27y² + 36xy²
<h3>How to evaluate the product?</h3>
The expression is given as:
(-2x-9y²)(-4x-3)
Expand the expression
8x² + 6x + 27y² + 36xy²
Hence, the value of the product expression (-2x-9y²)(-4x-3) is 8x² + 6x + 27y² + 36xy²
Read more about products at:
brainly.com/question/10873737
#SPJ1
Terrence is not correct.
Terrence is not correct because pi is an irrational number, and it goes on forever with no actual sequence.
Answer:
2x(x + 3)(2x - 1)
Step-by-step explanation:
Given
4x³ + 10x² - 6x ← factor out 2x from each term
= 2x(2x² + 5x - 3) ← factor the quadratic
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 3 = - 6 and sum = + 5
The factors are + 6 and - 1
Use these factors to split the x- term
2x² + 6x - x - 3 ( factor the first/second and third/fourth terms )
= 2x(x + 3) - 1(x + 3) ← factor out (x + 3) from each term
= (x + 3)(2x - 1)
Thus
4x³ + 10x² - 6x = 2x(x + 3)(2x - 1) ← in factored form
The store that is larger sells shirts at a better price because they have greater supply in comparison to the demand of shirts. The price is $2.99 because the larger store offers a discount of 10%.
Answer:
x = {-2, 2/3}
Step-by-step explanation:
2x = -4
x = -2
3x = 2
x = 2/3
x = {-2, 2/3}